Uji Penerapan Perbaikan Tanah Dasar Jenuh Air dengan Stabilitas Semen untuk Rekomendasi Desain Struktur Jalan di Kawasan Hamparan Perak Kab. Deli Serdang - M. Hadi Sofyan; Rizky Franchitika; Yudha Hanova (Jurnal Simetri Rekayasa, 2022)
Roads are an important factor in supporting agricultural development and making it more efficient. In the construction of agricultural roads in Lama Village, Hamparan Perak District, Deli Serdang Regency, the presence of soft soil is one of the problems in the construction of farm road construction. Embankments built on soft subgrade without reinforcement will experience a slide. so that it is necessary to strengthen and improve the subgrade soil to prevent road sliding. This study aims to increase the carrying capacity of water-saturated soil on agricultural land in Lama Village, Hamparan Perak District, Deli Serdang Regency. The method used in research on the improvement and strengthening of the subgrade for farm roads is cement stabilization. The variations in cement content used were 3%, 4%, and 5%. The bearing capacity of subgrade and stabilized soil will be tested using a dynamic cone penetrometer (DCP). From the research results, it can be seen that the average CBR value of subgrade is 0.65%. From the results of the comparison of soil CBR values, soil stabilization with a cement percentage of 3% shows a CBR value of 5.51%, or 6%, fulfilling the requirements to increase soil carrying capacity according to MDP 2017, where the minimum subgrade CBR for pavement design is 6%.